A framework and checklists for evaluating online learning in higher education - Hosie, Peter; Schibeci, R.; Backhaus, A. (Taylor and Francis, 2005)
A case is made in this paper for using checklists and context bound evaluations of online learning materials in higher education. Context bound evaluations complement traditional forms of evaluation of educational courseware, such as checklists. Context bound approaches are useful for indicating the pedagogical quality of online learning materials that may be productively used in conjunction with checklists to evaluate online learning. Edith Cowan University has developed a framework and checklists for assessing aspects of online pedagogical learning materials in higher education. These checklists, which are intended to be useful indicators of the areas where online learning materials are strong and to identify areas that may be deficient, and are a valuable screening and information gathering device to use when undertaking a context bound evaluation of learning materials. As such, the quality of the instructional design remains an important consideration in evaluating courseware, and such information needs to be presented in a form that is accessible and useful for educational developers and researchers. Comment and dissent is invited on the value of contextual evaluations to reinvigorate the debate over appropriate ways of evaluating online learning materials in higher education.